Fundamentals of Food Biotechnology - Lee, Byong H. (Wiley Blackwell, 2015)
Food biotechnology is the application of modern biotechnological techniques to the manufacture and processing of food, for example through fermentation of food (which is the oldest biotechnological process) and food additives, as well as plant and animal cell cultures. New developments in fermentation and enzyme technological processes, molecular thermodynamics, genetic engineering, protein engineering, metabolic engineering, bioengineering, and processes involving monoclonal antibodies, nanobiotechnology and quorum sensing have introduced exciting new dimensions to food biotechnology, a burg.